Bacopa monniera Attenuates Scopolamine-Induced Impairment of Spatial Memory in Mice. (13th February 2011) - Saraf, Manish Kumar; Prabhakar, Sudesh; Khanduja, Krishan Lal; Anand, Akshay
Abstract : Scopolamine, an anticholinergic, is an attractive amnesic agent for discerning the action of candidate antiamnesic drugs. Bacopa monniera Linn (Syn. Brahmi) is one such antiamnesic agent that is frequently used in the ancient Indian medical system. We have earlier reported the reversal of diazepam-induced amnesia with B. monniera. In this study we wanted to test if scopolamine-induced impairment of spatial memory can also be ameliorated by B. monniera using water maze mouse model. The objective of study was to study the effect of B. monniera on scopolamine-induced amnesia. We employed Morris water maze scale to test the amnesic effect of scopolamine and its reversal by B. monniera. Rotarod test was conducted to screen muscle coordination activity of mice. Scopolamine significantly impaired the acquisition and retrieval of memory producing both anterograde and retrograde amnesia. Bacopa monniera extract was able to reverse both anterograde and retrograde amnesia. We propose that B. monniera's effects on cholinergic system may be helpful for developing alternative therapeutic approaches for the treatment of Alzheimer's disease.